Updating Wikipedia in the School of Dentistry of the University of Florence - Marco Masoni; Omar Di Grazia; Maria Renza Guelfi (Firenze University Press, 2023)
Teachers of the Computer Science course of the School of Dentistry of the University of Florence have accepted the many invites from academic organizations, health and non-health related, to propose the teaching methodology of updating Wikipedia pages to the students. This study describes the educational strategy that was tested in a class of students attending the Computer Science course of the School of Dentistry. The used approach was analyzed from a qualitative and quantitative point of view, respectively through the administration of a satisfaction survey and the examination of the whole activity carried out by the students. Editing Wikipedia pages was globally appreciated by students who expressed satisfaction in participating in a shared knowledge production process that spreads beyond the academic sphere to address a real audience. The modified Wikipedia pages have aroused interest, receiving many visits from Internet users. The Computer Science course program includes a part related to Evidence Based Medicine, which transfers competencies that are propedeutic to update Wikipedia pages.   Aggiornamento di Wikipedia nel Corso di Laurea in odontoiatria e Protesi Dentaria dell'Università di Firenze. I docenti del corso di Informatica del Corso di Laurea in Odontoiatria e Protesi Dentaria (CLOPD) dell'Università di Firenze hanno accolto le numerose istanze provenienti da organizzazioni accademiche, sanitarie e non, che invitano a proporre la metodologia didattica di aggiornamento di Wikipedia agli studenti. In questo studio viene descritta la strategia formativa che è stata sperimentata in una classe di studenti frequentanti l'insegnamento di Informatica di CLOPD. L'approccio utilizzato è stato analizzato da un punto di vista qualitativo e quantitativo, rispettivamente attraverso la somministrazione di un questionario di gradimento e l'esame dell'attività svolta dagli studenti. L'aggiornamento di Wikipedia è stato globalmente apprezzato dagli studenti che hanno espresso soddisfazione nella partecipazione a un processo di produzione di conoscenza condivisa che si diffonde oltre l'ambito accademico per rivolgersi alla popolazione. Le pagine di Wikipedia modificate hanno destato interesse, ricevendo numerosi accessi dagli utenti della rete. Il programma del corso di Informatica prevede una parte relativa alla Evidence Based Medicine, che trasferisce competenze che risultano propedeutiche all'aggiornamento di Wikipedia.